A Wilkie Collins Chronology - Baker, W. author. aut Link
XV, 236 p.
Keywords: This book builds on a critical and scholarly revival of interest in Collins. Baker draws upon biographical revelations and the recent publication of Collins's letters to provide a unique insight into both the man and the writer. The volume will appeal to all students of Collins and those with an interest in the life of Nineteenth-century England.